Perception of rescued animals ownersof the importence of veterinary action in preventing zoonoses and promoting collective health (Research, Society and Development, 2025)
Zoonoses represent a major challenge to public health, requiring an integrated approach across different areas of knowledge. In this context, Veterinary Medicine plays a key role not only in the prevention and control of these diseases but also in promoting animal welfare and collective health. This study aimed to evaluate the perception of adopters of rescued animals regarding the relevance of veterinarians, through a questionnaire applied to guardians from the shelter Vira Lata – Vira Amor, in Cacoal – RO, Brazil. The findings indicate that although many participants recognize the clinical importance of veterinarians, there is still limited awareness of their contribution to public health and the One Health concept. These results highlight the need to expand the dissemination of the veterinarian’s role as a strategic agent in the protection of human, animal, and environmental health.